(untitled) (Conferencea, 2022)
This article examines the significance of the opening of the "Amateur Archaeologists’ Circle of Turkestan". With the opening of the circle, the first foundation stone was laid for studying the ancient history and culture of the peoples of Turkestan, including the Uzbeks.